2023
DOI: 10.1001/jamanetworkopen.2023.30856
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Associated With Overestimation of Oxygen Saturation by Pulse Oximetry in Patients Hospitalized With COVID-19

Ashraf Fawzy,
Tianshi David Wu,
Kunbo Wang
et al.

Abstract: ImportanceMany pulse oximeters have been shown to overestimate oxygen saturation in persons of color, and this phenomenon has potential clinical implications. The relationship between overestimation of oxygen saturation with timing of COVID-19 medication delivery and clinical outcomes remains unknown.ObjectiveTo investigate the association between overestimation of oxygen saturation by pulse oximetry and delay in administration of COVID-19 therapy, hospital length of stay, risk of hospital readmission, and in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Most recent studies investigating the impact of skin pigmentation on pulse oximeter accuracy among adults in clinical settings have substituted race and ethnicity for objective skin tone measurements. (9)(10)(11)(12)(13)(14)(15)(21)(22)(23) Laboratory studies of healthy volunteers that subjectively evaluated skin pigmentation have reported poor accuracy at low saturations (<80%) among darkly pigmented individuals compared with lighter pigmented individuals. (7,8) However, a reanalysis of proprietary healthy volunteer laboratory data reported no difference in pulse oximeter accuracy between Black and White volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent studies investigating the impact of skin pigmentation on pulse oximeter accuracy among adults in clinical settings have substituted race and ethnicity for objective skin tone measurements. (9)(10)(11)(12)(13)(14)(15)(21)(22)(23) Laboratory studies of healthy volunteers that subjectively evaluated skin pigmentation have reported poor accuracy at low saturations (<80%) among darkly pigmented individuals compared with lighter pigmented individuals. (7,8) However, a reanalysis of proprietary healthy volunteer laboratory data reported no difference in pulse oximeter accuracy between Black and White volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…(9)(10)(11)(12) Unrecognized hypoxemia is associated with delay in delivering COVID-19 therapy and higher readmission rate among COVID-19-infected patients. (13,14) However, past clinical studies have major limitations. First, race and ethnicity as recorded in the electronic medical record (EMR) was used as a surrogate for skin pigmentation, the presumed relevant physiologic parameter.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a retrospective study on 7126 patients with COVID-19 with a total of 32,282 concurrently measured SpO 2 and oxygen saturation levels in arterial blood (SaO 2 ) showed that SpO 2 values of self-identified Asian, Black, and Hispanic patients were overestimated and higher than SaO 2 by an average of 1.33% when compared to White patients, which led physicians to administer lower levels of oxygen [ 5 ]. In a follow-up study, researchers confirmed that skin tone can lead to delayed care as pulse oximeters may provide inaccurate readings in individuals of ethnicities that are known to have a higher prevalence of darker skin, affecting the timely administration of necessary treatments [ 6 ]. Moreover, researchers found that SpO 2 overestimation increased the risk of hospital readmission regardless of patient race, emphasizing the importance of accurate monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, pulse oximetry has become ubiquitous in the acute care setting despite evidence at the turn of the 21st century of the poor performance of pulse oximeters in this context ( 11 ). Likewise, warnings that pulse oximeters were less accurate in individuals with darker pigmentation went unheeded for decades by the medical community and regulators until investigations spurred by the coronavirus disease (COVID-19) pandemic highlighted the tendency of pulse oximeters to overestimate true oxygen saturation among individuals of racial and ethnic minorities and the adverse clinical consequences of this health disparity ( 12 16 ). In addition to evaluating the misclassification of the need for supplemental oxygen, Garnet and colleagues evaluated the risk factors for inaccurate estimation of arterial oxygen saturation by pulse oximetry.…”
mentioning
confidence: 99%